ROOT TRAINER MEDIA CONTAINING COCOPEAT AND PEAT TO SUPPORT GROWTH AND QUALITY OF RUBBER ROOTSTOCK ROOTS - Nur Eko Prasetyo; Budi Setyawan; Samijan Samijan; Nofitri Dewi Rinojati; Sumarmadji Sumarmadji (Jurnal Penelitian Tanaman Industri, 2020)
The physical and chemical properties of the growing medium for root trainer of rubber are critical to support plant growth. This study aimed to obtain the best medium for growing rootstock rubber seedlings in the root trainer.  Rubber clone PR 300 seeds were germinated for 21 days, then raised in root trainer pots for five months. The treatments evaluated were a mixture of cocopeat, Rawapening peat, and manure at different ratios.  The experiment was designed in a Randomized Block Design, three replications, 30 plants per replicate, totaling 720 plants. The observed variables were N, P, K, Mg, C-organic content, pH, and cation exchange capacity of cocopeat, peat, and manure, as well as plant growth (height, stem diameter, wet weight, and dry weight). ANOVA used for analyzing data, followed with the Duncan Multiple Range Test at 5% level. The results showed that there were three best root trainer media for PR 300 rubber rootstock seedlings were a mixture of cocopeat + peat (1:1), cocopeat + peat + manure (1:2:1), and cocopeat + peat + manure (2:1:1). The growth and compactness of the roots are outstanding, so the seedlings are easily removed from the root trainer pots without significant damage. Based on the initiation and cost, the best root trainer medium is a mixture of cocopeat + peat + manure (1: 2:1). It is necessary to study the use of other types of peat soils apart from Rawapening. Also, it needs to be observed further plant growth after inoculation with the stem and after planting in the field.Keywords : Planting medium, Rawapening peat, rubber clone PR 300.